2016
DOI: 10.1002/aenm.201601208
|View full text |Cite
|
Sign up to set email alerts
|

MoS2‐Based All‐Purpose Fibrous Electrode and Self‐Powering Energy Fiber for Efficient Energy Harvesting and Storage

Abstract: Here an all-purpose fibrous electrode based on MoS 2 is demonstrated, which can be employed for versatile energy harvesting and storage applications. In this coaxial electrode, ultrathin MoS 2 nanofilms are grown on TiO 2 nanoparticles coated carbon fiber. The high electrochemical activity of MoS 2 and good conductivity of carbon fiber synergistically lead to the remarkable performances of this novel composite electrode in fibrous dye-sensitized solar cells (showing a record-breaking conversion efficiency of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 79 publications
2
114
0
Order By: Relevance
“…Liu et al demonstrated that NiCo 2 S 4 nanoparticles grown on nitrogen and sulfur double‐doped graphene by solvothermal reaction . Due to the large surface area and abundant active sites provided by nanoflakes or nanosheets, such materials have been extensively explored in a wide range of electrochemical applications . Impressively, Ma et al showed that the self‐assembled ultrathin NiCo 2 S 4 nanoflakes grown on nickel foam (Ni) (NF) exhibited excellent electrocatalytic activity and stability for HER in alkaline solution .…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al demonstrated that NiCo 2 S 4 nanoparticles grown on nitrogen and sulfur double‐doped graphene by solvothermal reaction . Due to the large surface area and abundant active sites provided by nanoflakes or nanosheets, such materials have been extensively explored in a wide range of electrochemical applications . Impressively, Ma et al showed that the self‐assembled ultrathin NiCo 2 S 4 nanoflakes grown on nickel foam (Ni) (NF) exhibited excellent electrocatalytic activity and stability for HER in alkaline solution .…”
Section: Methodsmentioning
confidence: 99%
“…[7b] Thehollow graphenebased hybrid fibres promoted the capacitance by offering al arge interfacial surface to the electrolyte ions. [17] The uniform porous [11a] and dot-sheet structures [11c] had been developed to improve energy-storage capabilities by creating more ionic path channels and accessible surfaces.O ther alternative strategies,r egarding coating [18] and impregnated reaction methods [2b,19] that could efficiently introduce electroactive materials in fibres enabled FFSCs to perform excellent energy storage ability.I nt his respect, the energy densities were promoted by electrochemically active materials (e.g., metal oxides/sulfides (Mno 2 , [20] Co 3 O 4 , [21] MoS 2 [22] )a nd conducting polymer (polyaniline, [11b] polypyrrole [23] )) induced pseudo-capacitances.A lthough those approaches have im-proved the energy densities of FFSCs,t hese levels are still relatively too low to meet the demands of practical application. Twom ajor challenges need to be addressed:1 )The asprepared solid fibres have thicker diameters (dozens to hundreds of microns) and dense structures in which the outer surfaces are only used and micro/nanoscale effects are blocked.…”
Section: Introductionmentioning
confidence: 99%
“…Besides SS wires, carbon fibers (CFs) can also be used to build parallel‐like wire‐type DSSCPS . Jin et al first grew a layer of TiO 2 nanoparticles on the CF surface, followed by growing a MoS 2 nanofilm on the surface of TiO 2 .…”
Section: The Types Of Photo‐supercapacitorsmentioning
confidence: 99%